PERTUMBUHAN DAN HASIL TANAMAN KANGKUNG (Ipomoea reptans) PADA PEMBERIAN BEBERAPA KONSENTRASI EKOENZIM - Rahmawati, Aulia; Fadhlilah, Faiz; Fanaba, Yunus Khoirun; Salma, Kunti Malikhata; Indah, Diska (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
Land kangkung (Ipomea reptans) is one of the most popular horticultural crops in Indonesia because of its savory taste. In its cultivation, land kangkung does not require a large area so it can be cultivated in cities where land is generally limited. Cultivation can be done using polybags or hydroponics to overcome limited land. To achieve maximum kale productivity, plants need adequate nutrition by fertilizing. The limited availability of fertilizers and their high prices greatly affect the activities of farmers. Therefore, the use of ecoenzyme fertilizer is one solution to the problem. Besides being an additional organic nutrient in land kangkung, it can also act as an organic pesticide. The research was conducted in Wonosari Village, Kebumen District, Kebumen Regency. The study used a factorial complete randomized design (CRD). The first factor is the provision of ecoenzyme concentration as much as 3 levels, namely: K1 = Ecoenzyme 20 ml/liter of water, K2 = Ecoenzyme 30 ml/liter of water, K3 = Ecoenzyme 40 ml/liter of water. The second factor is the method of application of ecoenzyme which consists of 2 levels, namely P1 = watered, P2 = sprayed. There were 6 treatment combinations that were repeated 4 times. The results of this study showed that the provision of several concentrations of ecoenzyme and the method of application which became the treatment gave a different response to the growth of land kangkung plants but was not significant in the variables of plant height, number of leaves, and wet weight of plants. Based on these results, it can be concluded that ecoenzyme does not act as a nutrient enhancer for plants because the response to the growth and yield of kale plants has no significant effect. Further research should consider different doses of ecoenzyme administration that are more effective.